Achievement (not effort) makes people feel entitled to rewards - Corey Cusimano; Jin Kim; Jared Wong (Proceedings of the National Academy of Sciences, 2025)
It is common to say that people feel entitled to rewards—they think they have earned or deserve them—based on their effort and achievement. However, effort and achievement draw on different principles to justify reward. They can also conflict over when people should feel entitled to rewards. These observations raise the question: In everyday settings, do people feel entitled to rewards because of their effort, achievement, or some combination of the two? To determine how effort and achievement contribute to feelings of entitlement, we hired online workers and varied the feelings of effort and achievement that their work induced. We then let those workers decide how large of a bonus we then paid them. Achievement strongly predicted how much participants paid themselves. Hard work, by contrast, played little-to-no detectable role.